Mechanism of staphylococcal resistance to clinically relevant antibiotics - Brdová, Daniela; Ruml, Tomáš; Viktorová, Jitka (Drug resistance updates, 2024)
Staphylococcus aureus, a notorious pathogen with versatile virulence, poses a significant challenge to current antibiotic treatments due to its ability to develop resistance mechanisms against a variety of clinically relevant antibiotics. In this comprehensive review, we carefully dissect the resistance mechanisms employed by S. aureus against various antibiotics commonly used in clinical settings. The article navigates through intricate molecular pathways, elucidating the mechanisms by which S. aureus evades the therapeutic efficacy of antibiotics, such as β-lactams, vancomycin, daptomycin, linezolid, etc. Each antibiotic is scrutinised for its mechanism of action, impact on bacterial physiology, and the corresponding resistance strategies adopted by S. aureus. By synthesising the knowledge surrounding these resistance mechanisms, this review aims to serve as a comprehensive resource that provides a foundation for the development of innovative therapeutic strategies and alternative treatments for S. aureus infections. Understanding the evolving landscape of antibiotic resistance is imperative for devising effective countermeasures in the battle against this formidable pathogen.
Keywords: Animals; Staphylococcus aureus; Staphylococcal Infections; Microbial Sensitivity Tests; lidé; zvířata; stafylokokové infekce; mikrobiální testy citlivosti; antibakteriální látky; Anti-Bacterial Agents; Drug Resistance, Bacterial; bakteriální léková rezistence; Humans